Legal Protection Of Victims Of Mental Retardation Rape As A State Of Helplessness - Citra Arga Fajar Diva; Efrila Efrila; Ahmad Jaeni (Fakultas Hukum Dehasen, 2024)
Rape is a form of sexual violence that not only violates human rights, but also causes deep physical and psychological trauma to the victim. In this context, victims with mental retardation are in a very vulnerable position and are often unable to defend themselves or give legitimate consent. This condition makes them a group that needs special protection under the law. This study aims to analyze the legal protection of rape victims who experience mental retardation as a state of helplessness based on the applicable laws in Indonesia. Rape is a form of sexual violence that violates human rights and results in deep physical and psychological trauma for the victim. Victims with mental retardation have a higher vulnerability and require special protection. The approach used in this study is normative juridical, by analyzing related laws and regulations, including the Criminal Code (KUHP), Law Number 23 of 2004 concerning the Elimination of Domestic Violence, and Law Number 8 of 2016 concerning Persons with Disabilities. The results of the study show that although there are regulations that provide legal protection for rape victims, the implementation and enforcement of the law still face various obstacles. Factors such as social stigma, a lack of understanding of mental retardation, and limited resources in the justice system often hinder effective protection for victims. This study recommends increased socialization and training for law enforcement officials, as well as the provision of better support services for victims with mental retardation.